2015
DOI: 10.1016/j.physleta.2014.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Two-component feedback loops and deformed mechanics

Abstract: It is shown that a general two-component feedback loop can be viewed as a deformed Hamiltonian system. Some of the implications of using ideas from theoretical physics to study biological processes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…to mirror the formalism of conventional classical mechanics. He showed that this bracket remains invariant under specific representations of canonical transformations, and in [2] these were discussed in the setting of q-deformed groups. Duffin also proved a dissipative version of Liouville's theorem for statistical ensembles on phase space under the assumption that second derivatives ∂ 2 H/∂x i ∂y i are constant.…”
Section: Deformed Classical Mechanicsmentioning
confidence: 99%
See 4 more Smart Citations
“…to mirror the formalism of conventional classical mechanics. He showed that this bracket remains invariant under specific representations of canonical transformations, and in [2] these were discussed in the setting of q-deformed groups. Duffin also proved a dissipative version of Liouville's theorem for statistical ensembles on phase space under the assumption that second derivatives ∂ 2 H/∂x i ∂y i are constant.…”
Section: Deformed Classical Mechanicsmentioning
confidence: 99%
“…He called the dynamics psuedo-Hamiltonian. The same equations have also been shown to include models of very simple biological processes [2]. Properties of these systems are clearly different from those of conservative Hamiltonian systems since, reflecting dissipation, the Hamiltonian H is not an integral of motion…”
Section: Deformed Classical Mechanicsmentioning
confidence: 99%
See 3 more Smart Citations